2008
DOI: 10.1016/j.mito.2008.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mitochondrial functionality and calcium uptake in hypertensive rats as a function of age

Abstract: We studied whether mitochondrial functions and Ca 2+ metabolism were altered in Wistar Kyoto normotensive (WKY) and spontaneous hypertensive rats (SHR). Ca 2+ uptake was decreased in SHR compared to WKY rats. Accumulation of Ca 2+ was more efficient in WKY than in SHR rats. mΔΨ was lower in SHR compared to WKY rats. Basal complex IV activity was higher in SHR than WKY rats, whereas basal L-citrulline production, an indicator of nitric oxide synthesis, was decreased in SHR and dependent on Ca 2+ concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Cotransfection of MnSOD with eNOS prevented the rebound in ABP induced by eNOS overexpression in the SHR. Other studies reported an alteration in mCa 2þ handling in brain mitochondria during hypertension (89). These studies demonstrate the contribution of RNS, ROS, and mCa 2þ in regulating ABP through their actions on ETC complexes.…”
Section: Mitochondria and Hypertensionsupporting
confidence: 69%
“…Cotransfection of MnSOD with eNOS prevented the rebound in ABP induced by eNOS overexpression in the SHR. Other studies reported an alteration in mCa 2þ handling in brain mitochondria during hypertension (89). These studies demonstrate the contribution of RNS, ROS, and mCa 2þ in regulating ABP through their actions on ETC complexes.…”
Section: Mitochondria and Hypertensionsupporting
confidence: 69%
“…Various studies have suggested that mitochondrial Ca 2ϩ handling is disrupted by aging that could contribute to cell death because mitochondria play an important role buffering cytosolic Ca 2ϩ concentration (4,36,46). Importantly, reduced mitochondrial Ca 2ϩ uptake in aging may contribute to subsequent tissue injury.…”
Section: Tempol Effects On Mitochondria [Ca 2ϩ ] M Uptakementioning
confidence: 99%
“…Generally, mitochondrial matrix Ca 2+ can activate PDH at its E1α subunit and promote the transformation of pyruvic acid to acetyl‐CoA in the mitochondrial matrix . PDH is a key dehydrogenase, and its activity can also be blunted by angiotensin II through increasing the vascular PDH phosphorylation . However, the regulation of PDH activities in the vasculature in hypertension is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TRPC3 channel protein has been shown to localize in the inner membrane of mitochondria and to regulate mitochondrial Ca 2+ uptake . Other groups have investigated that the basal [Ca 2+ ] mito levels were different in heart, kidney, and brain tissues from SHRs compared with WKY rats, but the differences and functions of [Ca 2+ ] mito in the vasculature of SHRs remain unclear.…”
Section: Introductionmentioning
confidence: 99%